Incidence and distribution of coleopteran insect pests on rainfed maize (Zea mays L.) in upper himalayas of Jammu and Kashmir, India - Ahad, Ishtiyaq; Bhagat, R M; Monobrullah, Md (Journal of Phytology, 2011)
Experimental trail was conducted in free choice conditions at intermediate zone of Jammu and Kashmir, India during kharif season 2007. Various beetle populations viz. white grub (Holotrichia consaguinea), Blister beetle (Mylabris pustulata), flower eating beetle (Protatia alboquattata Vig.), wire worms (Melanotus communis Gyllenhal) and flea beetle (Phyllotera sp.) were observed at the experimental site. Among these pests H. consaguinea populations were found to be the dominating one. Correlation studies depicted that, both H. consaguinea adults and grubs were positively correlated with maximum and minimum temperatures. M. pustulata and P. alboquattata were negatively correlated with maximum and minimum temperatures, other beetles were positively correlated. H. consaguinea grubs, M. communis adults, were negatively correlated with relative humidity. M. pustulata and Phyllotreta sp. were positively correlated with relative humidity. As infestation of these insects is concerned wire worm, white grub larvae, white grub adult and blister beetle, fed on germinating seedlings, roots, leaves and silk, respectively however, both P. alboquattata and grain feeding flea beetle were found to feed on cob grains. Thus these beetles led to varying degree of damage and their distribution on maize plant.Ã‚Â